The Influence of Efficacy and Emotional Intelligence of Technical Secondary School Administrators' and Teachers' Professional Collaboration on Teachers' Job Satisfaction - Noraini, Abdullah Sani (2009)
The purpose of this study was to determine the influence of administrators' collective efficacy and emotional intelligence competencies and teachers professional collaboration on teachers' job satisfaction. Survey instruments were distributed to the respondents comprising of administrators (N=444) and teachers (N=1,426) of the Technical Secondary Schools in Malaysia. Four measures were used; Administrators' Collective Efficacy Scale (ACES), Emotional Competency Inventory-Version 2 (ECI-V2), Teacher Professional Collaboration Questionnaire (TPCQ) and Minnesota Job Satisfaction Questionnaire (MSQ). Data analysis started with evaluating data normality and psychometric integrity of the instruments using exploratory and confirmatory factor analyses. Several statistical analyses were employed to assess the hypotheses. Analyses include t-tests, bivariate correlation analysis, and stepwise and hierarchical regression analyses. Finally, path analysis was used to support earlier findings on the direct and indirect relationships of all the variables. Since there was significant difference between the administrators and the teachers' perceptions pertaining to the seven variables studied, data were analysed separately. Teachers' data only act as a support to the findings based on administrators' data. It was found that there were significant relationships between all the constructs studied. However, only teachers' professional collaboration, administrators' collective efficacy and emotional intelligence competency for relationship management (social skills) were predictors of teachers' job satisfaction. Administrators' collective efficacy and relationship management partially mediate the relationship between teachers' professional collaboration and teachers' job satisfaction. Several recommendations and implications were drawn from the study.